A global map of costal recreation values: Results from a spatially explicit based meta-analysis - Andrea Ghermandi; Paulo A. L. D. Nunes (Fondazione Eni Enrico Mattei (FEEM), 2011)
The welfare dimension of the recreational services provided by global coastal ecosystems is examined through a meta-analytical regression-based valuation approach. First, we construct a global, state-of-the-art database of stated and revealed preference estimates on coastal recreation, which includes also the grey literature and with the latest entry updated to February 2010. Second, the profile of each of the 253 observations of our dataset, which correspond to individual value estimates, was further enriched with characteristics of the built coastal environment (site accessibility, anthropogenic pressure, level of human development), characteristics of the natural coastal environment (presence of protected area, type of ecosystem, and marine biodiversity richness), geo-climatic factors (temperature and precipitation), as well as sociopolitical characteristics, such as the political stability index. In this context, the proposed meta-analytical valuation exercise explores the spatially explicit dimension of the values building upon Geographic Information System (GIS) tools. GIS are relied upon for the spatial characterization of the valued ecosystems, the determination of the role of spatially explicit variables in the meta analytical value transfer model, as well as for the value transfer exercise. The GIS characterization is observed to be extremely significant in explaining the spatial diversity of the estimates values and underlying explanatory factors. The resulting integrated valuation framework constitutes a worldwide première and it results in the first global map of the recreational value of coastal ecosystems. We argue that the presented global map may play an important role in studying the prioritization for the conservation of coastal areas from a social perspective.
Keywords: C53; Q26; Q57; R12; 330; Built Coastal Environment; Natural Coastal Environment; Ecosystem Service Valuation; Geographic Information Systems; Mapping Ecosystem Values; Marine Biodiversity; Scaling up; Spatial Analysis; Spatial Economic Valuation; Value Transfer